Hệ thống điều khiển tối ưu bình phương với ảnh hưởng của thời gian tính - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper analyses the influence of  computation time in digital control systems and prerents a method for designing a quadratic optimal regulator. A solution of the equivalent optimal control problem is proposed. The selection of weighting matrices is also discussed.